ПОВТОР КАК ФОРМАЛЬНЫЙ ПРИЕМ СИНТАКСИЧЕСКОГО ПАРАЛЛЕЛИЗМА - Магеррамова, Г. А. (Eurasian Journal of Philology Science and Education, 2015)
Syntactic parallelism like the main principle of the structure of epic texts like “Iqor’s Tale” and “Book of Dede Qorqud” has own formal methods. One of them is repetition. On the material given texts we noticed 2 type of repetition in the constructions with parallelism: lexical repetition and repetition of sentences. Such repetitions are one of the way of connecting different semantically units.